Welcome to Scribd. Sign in or start your free trial to enjoy unlimited e-books, audiobooks & documents.Find out more
Standard view
Full view
of .
P. 1
Chapter 18, Solution 1.

# Chapter 18, Solution 1.

Ratings: (0)|Views: 93|Likes:

### Availability:

See more
See less

10/24/2011

pdf

text

original

Chapter 18, Solution 1.
)2t()1t()1t()2t()t('
δ+δ+δ+δ=

2 j j j2 j
eeee)(F j
ωωωω
+=ωω

ωω=
cos22cos2  F(
ω
) =
ωω
j]cos2[cos2

Chapter 18, Solution 2.
<<=
otherwise,01t0,t )t(
-
δ
(t-1)
δ
(t)

f ”(t)
t
–
δ
’(t-1)

1-
δ
(t-1)01
f ‘(t)
t
f"(t) =
δ
(t) -
δ
(t - 1) -
δ
'(t - 1)Taking the Fourier transform gives-
ω
2
F(
ω
) = 1 - e
-j
ω
- j
ω
e
-j
ω
F(
ω
) =
2 j
1e) j1(
ω
ω
or F
∫
ω
=ω
10t j
dtet)(  But
∫
+=
c)1ax( aedxex
2axax

( )
=ω ω=ω
ω
102 j
)1t j(  je)(F
()
]
1e j1 1
j2
ω
ω

Chapter 18, Solution 3.
2t2, 21)t(',2t2,t 21)t(
<<=<<=

∫
ωω
ωω==ω
22222t jt j
)1t j( ) j(2 edtet21)(F
[ ]
)12 j(e)12 j(e 21
2 j2 j 2
ωω ω=
ωω

( )
[ ]
2 j2 j2 j2 j 2
eeee2 j 21
ωωωω
++ω ω=

( )
ω+ωω ω
2sin2 j2cos4 j 21
2
=
F(
ω
) =
)2cos22(sin  j
2
ωω
Chapter 18, Solution 4.
1 –2
δ
t–12
δ
t+1 –1g’2 0 –2t –2
δ
t1 –2
δ
t+11 –2
δ
t–12
δ
t+1 –1g”4
δ
(t) 0 –2t

4sin4cos4 e j2e24e j2e2)(G) j( )1t(2)1t(2)t(4)1t(2)1t(2g
j j j j2
+ωωω= ω+ω+=ωω δδδ++δ ++δ=
ωωωω
)1sin(cos 4)(G
2
ωω+ω ω=ω

Chapter 18, Solution 5.
10h’(t) –1 –2
δ
(t)1t
δ
(t+1) –
δ
(t–1)10h”(t) –1 –2
δ
’(t)1t
ωω=ω=ωω δδ+δ=
ωω
j2sin j2 j2ee)(H) j( )t(2)1t()1t()t(h
j j2
H(
ω
) =
ωωω
sin j2 j2
2